Evaluating the Performance of Sharq Dijila Water Treatment Plant - Al-Ani, Faris Hammoodi; Kadum, Wassel (Al-Khwarizmi Engineering Journal, 2011)
The study aims mainly to evaluate the performance of Sharq Dijila water treatment plant in removing turbidity for the period of 1-4-2001 to 31-3-2004. Daily data for turbidity of raw, clarified, filtered, and supplied water were analyzed. The results of the study showed that there is a wide variation in turbidity levels of raw water fluctuating between 10-1000 NTU with mean value of 41.3 NTU. Turbidity values of the clarified water varied between 1.4-77 NTU. Based on the turbidity value of 10 NTU and 20 NTU (the design maximum turbidity) the readings gave an acceptable percentage of 32.4% and 86% respectively. The turbidity of filtered water ranged between 0.2-4.5 NTU which are completely in compliance with Iraqi and WHO standards. In accordance with the American Environmental Protection Agency (USEPA) and based on the analysis of 2-day moving average of 5 NTU and 30-day moving average of 1 NTU, it was found that the filters operated at acceptable percentage of 100% and 45% respectively. Turbidity value of the supplied water averaged between 0.4-9.5 NTU which is higher than the turbidity of the filtered water due to the mixing of the water from all other filters. Also turbidity values from the unwashed filters are higher than the washed filters and the precipitation in the treated water reservoir. Based on the Iraqi Drinking Water Standard, USEPA 2-day and 30-day moving average, the supplied water was within the permissible limits of 98%, 98.6%, and 98.6% respectively.